6x - 7 + 4x = 13, solving for x here and i'm checking my work. Can you help me show my work?

Question

Asked 3/27/2012 12:25:46 PM

Updated 7/2/2014 11:10:47 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [7/2/2014 11:10:46 AM], Confirmed by andrewpallarca [7/2/2014 11:10:47 AM]

Expert answered|stan_r|Points 302|

Expert answered|eturker|Points 1673|

Question

Asked 3/27/2012 12:25:46 PM

Updated 7/2/2014 11:10:47 AM

0 Answers/Comments

This answer has been confirmed as correct and helpful.

Edited by andrewpallarca [7/2/2014 11:10:46 AM], Confirmed by andrewpallarca [7/2/2014 11:10:47 AM]

Rating

There are no new answers.

Simplify by Combining Like Terms:
1) x – 5x + 12x
2) 14xy3 – 22xy3 + 5xy3

Question

Updated 7/16/2014 2:56:26 AM

1 Answer/Comment

1) x – 5x + 12x = 8x

2) 14xy^3 – 22xy^3 + 5xy^3 = -3xy^3

2) 14xy^3 – 22xy^3 + 5xy^3 = -3xy^3

Added 7/16/2014 2:56:26 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/16/2014 4:04:29 AM]

Can you help me solve for x please. I need to show my work also. 6x - 7 + 4x = 13 **Weegy:** 6x - 8 > 4x + 26; 2x > 34; x > 17. The answer is: x > 17 **User:** I dont understand that. my question was solve for x. 6x - 7 + 4x = 13 **Weegy:** x = 17
**User:** can you explain how you got x = 17 please? (More)

Question

Expert Answered

Updated 3/27/2012 12:40:45 PM

1 Answer/Comment

6x - 7 + 4x = 13

6x + 4x = 13 + 7

10x = 20

x = 20/10

x = 2

6x + 4x = 13 + 7

10x = 20

x = 20/10

x = 2

Added 3/27/2012 12:40:45 PM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [7/2/2014 11:09:56 AM]

-12 – 48 ÷ 6 x 32 + 10 **Weegy:** -12-48= -60 /6 = -10 * 32 = -320 + 10 = -310 (More)

Question

Expert Answered

Updated 7/2/2014 11:09:14 AM

1 Answer/Comment

-12 – 48 ÷ 6 x 32 + 10

= -12 - 8 x 32 + 10

= -12 - 256 + 10

= -12 - 246

= -258

= -12 - 8 x 32 + 10

= -12 - 256 + 10

= -12 - 246

= -258

Added 7/2/2014 11:09:13 AM

This answer has been confirmed as correct and helpful.

Applying PEMDAS, simplify these expressions: -12 – 48 ÷ 6 x 32 + 10

Question

Updated 5/31/2014 5:13:20 PM

1 Answer/Comment

-12 – 48 ÷ 6 x 3^2 + 10;

-12 - 48 ÷ 6 x 9 + 10;

-12 - 8 x 9 + 10;

-12 - 72 + 10;

-12 - 62 = -74

-12 - 48 ÷ 6 x 9 + 10;

-12 - 8 x 9 + 10;

-12 - 72 + 10;

-12 - 62 = -74

Added 5/31/2014 5:13:20 PM

This answer has been confirmed as correct and helpful.

9x – 2 = 4x + 3 can you help me solve for x and show my work, please? **Weegy:** Sure thing.
9x-2=4x+3
9x-4x=3-2
5x=1
x=1/5 (More)

Question

Expert Answered

Updated 7/2/2014 11:06:40 AM

1 Answer/Comment

9x – 2 = 4x + 3;

9x - 4x = 3 + 2;

5x = 5;

x = 1

9x - 4x = 3 + 2;

5x = 5;

x = 1

Added 7/2/2014 11:06:40 AM

This answer has been confirmed as correct and helpful.

31,243,310

questions answered

denyang

$216.05

Hearts 4,587 Views 1,281,439 Streams 565

phpmicro

$186.90

Hearts 3,833 Views 832,745 Streams 286

maydj

$174.15

Hearts 3,825 Views 956,287 Streams 385

wildflower14344

$163.15

Hearts 4,147 Views 1,608,248 Streams 549

emdjay23

$152.05

Hearts 3,392 Views 757,559 Streams 260

miyaka

$150.25

Hearts 3,210 Views 710,315 Streams 418

Flora1988

$141.95

Hearts 3,043 Views 484,636 Streams 242

Peachygguk97

$122.05

Hearts 2,642 Views 308,449 Streams 172

There are no comments.